Onset and frequency of depression in post-COVID-19 syndrome: A systematic review. (December 2021) - Renaud-Charest, Olivier; Lui, Leanna M.W.; Eskander, Sherry; Ceban, Felicia; Ho, Roger; Di Vincenzo, Joshua D.; Rosenblat, Joshua D.; Lee, Yena; Subramaniapillai, Mehala; McIntyre, Roger S.
Abstract: Following recovery from COVID-19, an increasing proportion of individuals have reported the persistence and/or new onset of symptoms which collectively have been identified as post-COVID-19 syndrome by the National Institute for Health and Care Excellence. Although depressive symptoms in the acute phase of COVID-19 have been well characterized, the frequency of depression following recovery of the acute phase remains unknown. Herein, we sought to determine the frequency of depressive symptoms and clinically-significant depression more than 12 weeks following SARS-CoV-2 infection. A systematic search of PubMed, Ovid Medline and Google Scholar for studies published between January 1, 2020 and June 5, 2021 was conducted. Frequency and factors associated with depression in post-COVID-19 syndrome were recorded and qualitatively assessed through narrative synthesis. Methodological quality and risk of bias was assessed using a modified version of the Newcastle-Ottawa Scale (NOS) for prospective cohort studies. Of 316 articles identified through our systematic search, eight studies were included. The frequency of depressive symptoms +12 weeks following SARS-CoV-2 infection ranged from 11 to 28%. The frequency of clinically-significant depression and/or severe depressive symptoms ranged from 3 to 12%. The severity of acute COVID-19 was not associated with the frequency of depressive symptoms. However, the component studies were highly heterogeneous with respect to mode of ascertainment, time of assessment, and location and age of patients. The majority of studies did not include an unexposed control group. Future research should endeavour to produce a standardized classification of post-COVID-19 syndrome, and as well as include unexposed control groups.